The influence of health education card games utilizing the Roy's Adaptation Model on enhancing resilience in adolescents - Ike Puspitaningrum; Sukma Diani Putri; Evi Supriatun; Sri Endang Pujiastuti (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Adolescent mental health, particularly among nursing students exposed to substantial academic and emotional demands, requires effective and theory-driven resilience interventions. Although gamified health education shows potential, its integration with established nursing theories such as Roy’s Adaptation Model (RAM) remains limited. Objective: This study evaluated the effectiveness of a RAM-based educational card game in enhancing mental resilience among late adolescent nursing students. Methods: A quasi-experimental pretest–posttest control group design was conducted involving 118 nursing students (59 intervention; 59 control) from Politeknik Negeri Indramayu, Indonesia. The intervention group participated in a two-week educational card game program (60–90 minutes per session) designed to address RAM’s four adaptive modes: physiological, self-concept, role function, and interdependence. The control group received standard health education booklets. Resilience was assessed using the Adolescent Resilience and Adaptation Scale (ARAS). Due to non-normal data distribution, the Wilcoxon Signed-Rank and Mann–Whitney U tests were applied. Results: The intervention group demonstrated a significant increase in resilience from pretest to posttest (Z = −6.74, p < 0.001). Post-intervention resilience scores were significantly higher in the intervention group compared with the control group (U = 719, p < 0.001), with a medium-to-large effect size (r = 0.506). Conclusion: These findings indicate that a RAM-based educational card game is an effective and practically meaningful approach to strengthening resilience in late adolescent nursing students. This intervention offers a promising, theory-informed strategy for mental health promotion and supports the integration of resilience-building programs into nursing education curriculum.